New opportunities and perspectives for the electric vehicle operation in smart grids and smart homes scenarios - Monteiro, Vítor Duarte Fernandes (2017)
New perspectives for the electric vehicle (EV) operation in smart grids and smart homes context are presented. Nowadays, plugged-in EVs are equipped with on-board battery chargers just to perform the charging process from the electrical power grid (G2V – grid-to-vehicle mode). Although this is the main goal of such battery chargers, maintaining the main hardware structure and changing the digital control algorithm, the on-board battery chargers can also be used to perform additional operation modes. Such operation modes are related with returning energy from the batteries to the power grid (V2G- vehicle-to-grid mode), constraints of the electrical installation where the EV is plugged-in (iG2V – improved grid-tovehicle mode), interface of renewables, and contributions to improve the power quality in the electrical installation. Besides the contributions of the EV to reduce oil consumption and greenhouse gas emissions associated to the transportation sector, through these additional operation modes, the EV also represents an important contribution for the smart grids and smart homes paradigms. Experimental results introducing the EV through the aforementioned interfaces and operation modes are presented. An on-board EV battery charger prototype was used connected to the power grid for a maximum power of 3.6 kW.